SMALL-SCALE CAPTURE FISHERIES MANAGEMENT STRATEGY (ARTISANAL FISHERIES) IN TEGAL REGENCY WATERS - Dwi Purwanto; Etty Riani; Hedi Heryadi (Universitas Mataram, 2025)
Small-scale capture fisheries play a crucial role in coastal community livelihoods but face challenges of overexploitation and low competitiveness. This study aimed to analyze the characteristics and socio-economic conditions of small-scale capture fisheries and develop sustainable management strategies in Tegal Regency. The study was descriptively and conducted in August 2023 using surveys and interviews with 60 fishers and stakeholders. Data were analyzed using the SWOT (Strengths, Weaknesses, Opportunities, Threats) method. The main fishing gears were gemplo, badong, trammel net, handline, payang, and arad net, with the highest productivity (0.59 tons/trip) from gemplo. Most fishers graduated from elementary school (91.67 %) and earned moderate incomes (Rp 2.19–4.23 million). SWOT analysis showed an aggressive strategy position (Quadrant I), prioritizing port optimization for training and insurance programs, value-added development through export and cold storage, and institutional strengthening via HNSI and KUB.